Can the aggregate implied cost of capital be used to predict excess returns on the JSE - Museka, Zvikomborero Austen (My University, 2016)
Return predictability is a principle which has gained increased academic and industry interest over the recent years. A lot of work has been done using different accounting and financial parameters to predict returns on international stock markets. This research sought to find out if we can use the Aggregate Implied Cost of Capital as a proxy for returns on the JSE. The findings show that the ICC is a proxy for returns on the JSE with a reasonably acceptable explanatory power
Master of Management in Finance & Investment Faculty of Commerce Law and Management Wits Business School University of The Witwatersrand 2016